Parenting Style and Emotional Resilience: The Role of Democratic Parenting in Single-Parent Families - Irbathy, Shafa Alistiana; Fahma, Naomi; Albany, Sulistiono Shalladdin; Suparmun, Arifah Cahyo Andini; Nurshanti, Yuliana; Masruroh, Ade (COUNS-EDU: The International Journal of Counseling and Education, 2025)
Parental style shapes a child’s character and emotional resilience, particularly within single-parent families. This study explores how single parents implement democratic parenting and how it influences the emotional resilience of children aged 7 and 8. Employing a descriptive qualitative method, data were collected through in-depth interviews, observation, and documentation involving three single parents and two teachers at SD Muhammadiyah Tonggalan. Thematic analysis revealed that democratic parenting—characterized by open communication, rule negotiation, and consistent emotional support—could still be applied effectively by single parents despite their dual-role burdens. Children raised under this approach exhibited high levels of emotional resilience, including emotional regulation, conflict resolution, frustration tolerance, and confidence in social interaction. External factors such as teacher and peer support also significantly enhanced emotional resilience. These findings highlight the strategic role of schools and community programs in supporting single parents in adopting effective parenting strategies for optimal child development.